Nilai Etis Relasi Individu Sosial dalam Filsafat Pierre Teilhard de Chardin - Sri Sudarsih (Prodi Antropologi Fakultas Ilmu Budaya Universitas Diponegoro, 2020)
A harmonious life is as expected by every member of the community. This study aims to find ethical values in the relations of social individuals in the Philosophy of Pierre Teilhard de Chardin which can be used as an alternative to the development of a sense of solidarity and ownership among individuals. This research is a qualitative research with the material object is the relation of social individuals in the philosophy of Teilhard de Chardin, while the formal object is an ethical value. The method used in this research is the synthesis analysis method with methodical interpretation. The formulation of the results in this study is that individuals really need the existence of others. Individuals must build relationships with others by giving and receiving, mutual respect, tolerance, and mutual respect. Individuals can find their identity when they are able to build relationships with other individuals. This relationship must be filled with love so that it will bring each individual to perfection. This point is optimistic that can be achieved by each individual. Human values are reflected in the attitude of each individual in his relationship with others in love.